2007
DOI: 10.1007/s10562-007-9369-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel Au/TiO2/Al2O3 · xH2O catalysts for CO oxidation

Abstract: Á xH 2 O (x = 0-3) catalysts were prepared by assembling gold nanoparticles on neat and TiO 2 -modified Al 2 O 3 , AlOOH, and Al(OH) 3 supports, and their catalytic activity in CO oxidation was tested either as synthesized or after on-line pretreatment in O 2 -He at 500°C. A promotional effect of TiO 2 on the activity of gold catalysts was observed upon 500°C-pretreatment. The catalyst stability as a function of time on stream was tested in the absence or presence of H 2 , and physiochemical characterization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
(101 reference statements)
1
17
0
Order By: Relevance
“…(2) can we find active gold catalysts based on previously overlooked supports (e.g., metal phosphates)? In addition, the effects of the crystal phase [65,82,[96][97][98][99][100], size [99,[101][102][103][104][105][106][107][108], and shape [45,[108][109][110][111][112][113][114] of solid supports on the catalytic performance are also of interest. Below we first present the development of Au/SiO 2 and Au/metal phosphate catalysts in our group, and then highlight recent findings on the effects of the particle size and shape of solid supports.…”
Section: General Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…(2) can we find active gold catalysts based on previously overlooked supports (e.g., metal phosphates)? In addition, the effects of the crystal phase [65,82,[96][97][98][99][100], size [99,[101][102][103][104][105][106][107][108], and shape [45,[108][109][110][111][112][113][114] of solid supports on the catalytic performance are also of interest. Below we first present the development of Au/SiO 2 and Au/metal phosphate catalysts in our group, and then highlight recent findings on the effects of the particle size and shape of solid supports.…”
Section: General Considerationsmentioning
confidence: 99%
“…Indeed, Fe 2 O 3 , TiO 2 , NiO x , and CoO x have been classified as "active" supports because they are reducible and can activate and store oxygen, whereas Al 2 O 3 and SiO 2 were classified as "inert" supports because they may not be able to supply reactive oxygen for CO oxidation [117]. Nevertheless, Au/Al 2 O 3 [82,109,118,119] and Au/SiO 2 [93,95,[120][121][122][123][124][125] can be active for CO oxidation. For example, Au/SiO 2 prepared via gas-phase grafting of dimethyl gold acetylacetonate exhibited high activity in CO oxidation [120][121][122].…”
Section: Au/siomentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that gold on reducible supports (e.g., TiO 2 , CeO 2 , Fe 2 O 3 ) exhibits higher activity in CO oxidation than gold on non-reducible supports (e.g., Al 2 O 3 , SiO 2 ) because the former can activate oxygen [6][7][8]. Nevertheless, properly prepared Au/Al 2 O 3 [9][10][11] and Au/SiO 2 [12][13][14][15][16][17][18][19] can also show high activities in CO oxidation.…”
Section: Introductionmentioning
confidence: 99%